The Cold War in Colombia. A Necessary Periodization - González Cepeda, Liborio (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article presents a periodization of the Cold War in Colombia, the confrontation between the powers and power blocks transferred to different countries, creating a problem of relations inside each of them. The study shows the existance of three great periods, coinciding in some points with periodizations of the international conflict, but also possessing particularities that respond to the political development of the country. Based on the fact that the Cold War was an international war of ideas that assumed the interior ofdifferent nations as its scenery, its periodization must equally take into account the particularities of the different cases, and the conflicts between the different forces struggling internally for power. As a confrontation for societal projects, this study is framed in political history and its documentary sources arethe different actions, events, and policies that explain the historical development of the country, from the perspectve of  its different actors. Nevertheless, as part of an international conflict, it also uses documents that narrate and describe the principal actions promoted by the United States specifically for the Colombian case and in general for the whole continent.